2003
DOI: 10.1046/j.1365-2249.2003.02186.x
|View full text |Cite
|
Sign up to set email alerts
|

Complement component C7 deficiency in a Spanish family

Abstract: SUMMARYDifferent genetic mutations have been described in complement component C7 deficiency, a molecular defect which is clinically associated with an increased susceptibility to neisserial recurrent infections, although some cases remain asymptomatic. In this work we report the genetic bases of C7 deficiency in one Spanish family. Exon-specific PCR and sequencing revealed a novel point mutation at nucleotide 615 (exon 6) leading to a stop codon (UGG to UGA) in the patient, his mother, and sister. This transv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…Halle and coworkers found the G357R mutation among Israeli Moroccan Jewish individuals 18 . The mutation was found also in two siblings with C7 deficiency from a highly inbred Arab population living in the lower Galilee region of Israel, a place where Sephardic Jews have lived for many generations 19 and very recently in two heterozygous C7 deficient siblings in our population 14 . Interestingly, patient 1 was from Gypsy ethnical background.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Halle and coworkers found the G357R mutation among Israeli Moroccan Jewish individuals 18 . The mutation was found also in two siblings with C7 deficiency from a highly inbred Arab population living in the lower Galilee region of Israel, a place where Sephardic Jews have lived for many generations 19 and very recently in two heterozygous C7 deficient siblings in our population 14 . Interestingly, patient 1 was from Gypsy ethnical background.…”
Section: Discussionsupporting
confidence: 61%
“…and the position of mutations described to date (numbered from 1 to 15), and the two novel mutations found in our study (16,17). Mutations described previously: 1, G>A transition at the 3′ acceptor site of intron 1; 17 2, R198Q; 21 3, deletion of around 6·8 kbp including exons 7 and 8; 17 ; 22 4, a G>A transversion at the 5′ splice donor site of intron 7; 21,23 5, G357R; 14,17–19 6, R499S; 24 7, 1929delC; 21 8, E631X; 13 9, E660Q; 21 10, R665H; 21 11, 2137delTG or 2138delGT/2139delTG; 12 12, C728X; 12 13, 2350delG; 21 14, T>C transversion at the splice donor site of intron 16; 21,23 15, W183X 14 . Circled mutations 5, 16 and 17 indicate mutations found in the patients in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The activation of the complement cascades allows the killing of microbes and the regulation of other immune processes. Many studies have indicated deficiencies in complement components with effects on human/ animal health, for instance, bacterial meningitis infection of hosts (Eng 1980;Haeney et al 1980;Ross and Densen 1984;Inai et al 1989;Fukumori and Horiuchi 1998;Zhu et al 2000;Vazquez-Bermudez et al 2003). These authors have also demonstrated that most deficiencies are associated with polymorphisms present in the molecular structure of at least one complement component.…”
Section: Introductionmentioning
confidence: 80%